DYNAMIC MECHANISM DESIGN FOR A GLOBAL COMMONS - Harrison, Rodrigo; Lagunoff, Roger (International economic review (Philadelphia), 2017)
We model dynamic mechanisms for a global commons. Countries value both consumption and conservation of an open access resource. A country's relative value of consumption to conservation is privately observed and evolves stochastically. An optimal quota maximizes world welfare subject to being implementable by Perfect Bayesian equilibria. With complete information, the optimal quota is first best; it allocates more of the resource each period to countries with high consumption value. Under incomplete information, the optimal quota is fully compressed: Identical countries receive the same quota even as environmental costs and resource needs differ. This is true even when private information is negligible.